Проблеми неповних сімей у контексті демографічного розвитку - Ничипоренко, С.В. (Інститут демографії та соціальних досліджень НАН України, 2006)
В статье автор раскрывает основные причины и факторы появления неполных семей, особое внимание отводится проблемам материнских семей. Дается анализ неполных семей по данным Всеукраинской переписи населения 2001 года. Предложены возможные пути решения некоторых проблем, с которыми сталкиваются неполные семьи. In the publication the author opens principal causes and factors of occurrence of incomplete families, the special attention is allocated to problems of single-mother families. The analysis of incomplete families according to Ukranian population censuses of 2001 is given. Possible ways of solution of some problems with which incomplete families collide are offered.